Pelatihan Kepemimpinan Demokratis Untuk Menghasilkan Produk Inovatif Di Koperasi Konsumen Wanita Sekar Kartini Jember - Muhammad Fanani; Endang Lifchatullaillah; Lailatus Sa’diah (jurnal ABDIMAS Indonesia, 2023)
Leadership is one description of an institution as a process of influencing other people in a certain scope to work together in a productive way and in pleasant conditions. (Tappen, 1995 in Sitorus and Panjaitan, 2011). As a leader you should be able to create an atmosphere work that creates a new and innovative atmosphere for its staff in achieving goals to be better and obtain higher results than before. It is described that an effective leader is considered to be a person who can read situations and conditions and is able to overcome problems with responsibility and integrity and has good ethics (Muninjaya, 2004). Innovative work behavior is the creation, introduction and implementation of new ideas or ideas in work, either as a group or organization in an effort to improve performance in an organization (Jansen, 2000). As explained above, assistance is needed for business actors or employees who are willing to become respondents to take part in Democratic Leadership Training carried out by researchers. The output target achieved from this research is the production of scientific publications in national journals with ISSN.